Written Corrective Feedback for Students’ Research Proposal in English: What Do Students and Lecturers Prefer and Why? - Fortunasari Fortunasari; Nunung Fajaryani; Bunga Ayu Wulandari; Khairunnisa Khairunnisa (Universitas Jambi, Indonesia, 2021)
The purposes of this study were to describe types of written corrective feedback applied by the lecturers on students’ research proposal and to find out the favorable types of written corrective feedback for the students of English study program at a public university in Jambi. This research used a questionnaire to collect the data from students and lecturers. The results of this research revealed that there were three types of written corrective feedback that were often used by the lecturers. They were direct corrective feedback, grammatical description, and electronic corrective feedback from metalinguistic feedback. Additionally, there were four types that sometimes were used by the lecturers. They were indirect corrective feedback, error codes by metalinguistic feedback, unfocused and focused feedback. The last type was reformulation. It was rarely used by the lecturers. The results also showed that direct, electronic, and unfocused corrective feedbacks were very favorable for students while a brief grammatical description (metalinguistic), focused feedback, error codes (metalinguistic), and reformulation feedback were somewhat favorable. The last type was indirect corrective feedback which was very unfavorable for the students. Implications and recommendations are discussed.